ANALISIS PENGELOLAAN SAMPAH BERKELANJUTAN PADA WILAYAH PERKOTAAN DI INDONESIA - Ade Fia Rahmawati; Amin Amin; Rasminto Rasminto; Fetro Dola Syamsu (Bina Gogik: Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2021)
Abstract This study aims to determine the municipal solid waste management system in Indonesia and to determine the extent to which the sustainable concept is applied in municipal solid waste management. The research method used is a literature study, with descriptive writing techniques and making books, encyclopedias, and data from previous studies that have relevance as research analysis materials. The results of the analysis show that urban area produces 70% of waste generation and as much as 32% of unmanaged waste. This is because the level of public concern for the environment is low, only 0.72. The average monthly expenditure figure as a form of meeting food and non-food needs increases to a minimum value of Rp. 400,000 and a maximum of Rp. 1,200,000. Humans cannot be separated from activities that produce waste so that the form of reduction and management is the key to solving the waste problem.that the activities of urban communities have resulted in quite high waste generation. The implementation of the waste management system still refers to the conventional method with the form of collect-transport-waste habits and burdens the burden of waste management at the final stage with a reactive approach so that it can be said that the implementation of municipal solid waste management is still low. Efforts to achieve the goals in the SDGs and fulfill the existing aspects of sustainable municipal waste management that have not been implemented properly, it is necessary to increase environmental awareness by emphasizing socialization and education for the community in seeing the waste itself so as to form behavior patterns that support the reduction 1and processing of municipal waste. Keywords: Implementation Analysis, Sustainable Waste Management, Characteristics of Municipal Waste.